2018
DOI: 10.14202/vetworld.2018.874-882
|View full text |Cite
|
Sign up to set email alerts
|

Hematological parameters and selected intestinal microbiota populations in the Indonesian indigenous crossbred chickens fed basal diet supplemented with multi-strain probiotic preparation in combination with vitamins and minerals

Abstract: Aim:The aim of this study was to investigate the effect of dietary supplementation with multi-strain probiotic preparation in combination with vitamins and minerals on the hematological parameters and selected intestinal microbiota populations in the Indonesian indigenous crossbred chickens.Materials and Methods:A total of 240 one-day-old Indonesian indigenous crossbred chicks were raised for 10 weeks. The chicks were distributed to one of four groups, i.e., chicks receiving basal diet without any additive (CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 26 publications
3
12
0
Order By: Relevance
“…Probiotic supplementation with heat stress conditions significantly improved the hematological measurements in broiler chicks ( 59 ). However, Sugiharto et al ( 60 ) reported that probiotics have no effect on the chicks' hematology in normal environmental conditions. On the other side, the results of the leukogram were negatively affected under thermal stress.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotic supplementation with heat stress conditions significantly improved the hematological measurements in broiler chicks ( 59 ). However, Sugiharto et al ( 60 ) reported that probiotics have no effect on the chicks' hematology in normal environmental conditions. On the other side, the results of the leukogram were negatively affected under thermal stress.…”
Section: Discussionmentioning
confidence: 99%
“…Whatever benefit was conferred by the access to the hedgerow appeared to be preferentially allocated to production performance in the Cornish cross and immune function in the Red rangers. This is makes sense when considering the intended use for each genotype; fast growing Cornish cross were developed to achieve maximum growth rates in the sterile, tightly regulated environment of conventional indoor poultry-houses (Aviagen, 2018), whereas slower growing Red rangers retain the ancestral ability to allocate resources into the development of energetically expensive adaptive mechanisms such as hemodynamic cooling and immune surveillance (Donkoh, 1989;Wideman et al, 1994;Sugiharto et al, 2018). These findings are consistent with a phenomenon that has been well-documented in broiler chickens, in which there exists a genetic trade-off between maximum production performance and the ability to adapt to environmental challenges (Cahaner and Leenstra, 1992;Deeb and Cahaner, 2002;Ask et al, 2006;Azad et al, 2010;Castellini et al, 2016;Duangjinda et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, feed additives such as probiotics are needed to improve the productivity and performance of Peking ducks. Probiotics are a group of beneficial microbes used to influence the host through the repair of the microorganisms in the digestible tract [4]. The most commonly used probiotic microorganisms are the Lactobacillus and the Bifidobacteria strains [5].…”
Section: Introductionmentioning
confidence: 99%